Increased levels of forkhead box M1B transcription factor in transgenic mouse hepatocytes prevent age-related proliferation defects in regenerating liver - Wang, Xinhe (The National Academy of Sciences, 2001)
The forkhead box (Fox) family of transcription factors share homology in the winged helix/forkhead DNA-binding domain and play important roles in regulating cellular proliferation, differentiation, longevity, and cellular transformation. Forkhead box M1B (FoxM1B) is a ubiquitously expressed member of the Fox transcription factor family whose expression is restricted to proliferating cells and that mediates hepatocyte entry into DNA synthesis and mitosis during liver regeneration. Recent cDNA microarray studies indicated that age-related defects in cellular proliferation are associated with diminished expression of the FoxM1B transcription factor. Here, we show that increased levels of FoxM1B in regenerating liver of old transgenic mice restore the sharp peaks in hepatocyte DNA replication and mitosis that are the hallmarks of young regenerating mouse liver. Restoration of the young regenerating liver phenotype is associated with increased expression of numerous cell cycle regulatory genes that include cyclin D1, cyclin A2, cyclin F, cyclin B1, cyclin B2, Cdc25B, and p55cdc. Cotransfection assays in the human hepatoma HepG2 cell line demonstrated that FoxM1B protein stimulated expression of both the cyclin B1 and cyclin D1 promoters, suggesting that these cyclin genes are a direct FoxM1B transcriptional target. These results suggest that FoxM1B controls the transcriptional network of genes that are essential for cell division and exit from mitosis. Our results indicate that reduced expression of the FoxM1B transcription factor contributes to the decline in cellular proliferation observed in the aging process.